Implementasi N-Modular Redundancy pada Vehicle Accident Report System - Bayu Bagus Prabowo; Rakhmadhany Primananda; Agung Setia Budi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Vehicles are one of the necessities needed by humans at this time, especially in Indonesia, where the number of vehicle accidents is quite large, especially in remote areas, and far from health facilities. For that we need a vehicle accident report system, which is reliable and accurate. The tool must be able to detect accidents accurately and be able to send messages to the victim's family. However, in an accident, the vehicle will be in a condition that can cause damage to components or modules as a whole. These problems can cause the device to be unable to detect accidents. Therefore, the system must be equipped with the N-Modular Redundancy method, as a method to disguise errors that occur in the module and allow the tool to continue to work, even if there is damage. N-Modular Redundancy or NMR is a method based on the principle of the Triple Modular Redundancy or TMR method, but this method uses